THE EFFECT OF STRATEGIC LEADERSHIP STYLE AND ORGANIZATIONAL CLIMATE ON EMPLOYEES' ORGANIZATIONAL COMMITMENT THROUGH JOB SATISFACTION AT PURBALINGGA PALM FLOWER COMPANY: THE EFFECT OF STRATEGIC LEADERSHIP STYLE AND ORGANIZATIONAL CLIMATE ON EMPLOYEES' ORGANIZATIONAL COMMITMENT THROUGH JOB SATISFACTION AT PURBALINGGA PALM FLOWER COMPANY - Bahy, Lanang Mustika; Yusuf, M. (PENANOMICS: International Journal of Economics, 2025)
This study aims to determine and analyze the influence of strategic leadership style and organizational climate on employee organizational commitment through job satisfaction at the Purbalingga Palm Flower Company. The method used in this study was an associative method with a quantitative approach. The sample size was 89 respondents. The sampling technique used was non-probability sampling with a saturated sampling technique. The analysis used SEM-PLS. The results of this study are: (1) leadership style has a positive and significant effect on job satisfaction, (2) organizational climate has a positive and significant effect on job satisfaction, (3) leadership style has a positive and significant effect on organizational commitment, (4) organizational climate has a positive and significant effect on organizational commitment, (5) job satisfaction has a positive and significant effect on organizational commitment, (6) leadership style has a positive and significant effect on organizational commitment through job satisfaction, and (7) organizational climate has a positive and significant effect on organizational commitment through job satisfaction.